STORYTELLING : STIMULATING CHILDREN’S LEADERSHIP - Ashari, Novita; Mustamin, Fitriani; Khaeriyah, Ummul; Asnar, Armi Nadilah; Salmawati, Salmawati; Rasyid, Dian Rahma; Bakri, Nurdiana (Journal of Early Childhood Education (JECE), 2022)
The formation of a leadership spirit that is still minimal is a problem in this research. The results of initial observations showed that children were not confident, and shy, parents of children waited at school until learning was finished, and low cooperation between children when teachers gave group activities. This study aims to form a leadership through the storytelling about the history of the Prophet's trade in group B children at RA DDI Majennang Suppa. This research method uses descriptive qualitative research in which the researcher describes the actual findings from the data in the field. The research data was collected by using interview, observation and documentation techniques. In inculcating leadership , indicators are needed including self-confidence, independence, discipline, honesty, responsibility, and cooperation. Based on the findings of the research conducted, the researchers obtained the results that the application of the storytelling history of the Prophet's trade can form the leadership of group B children in RA DDI Majennang.